An epidemiological study to assess the awareness of hepatitis B infection in the dental students, college staff, practitioners, and auxiliary staff in city of Maharashtra - Atul A Pandharbale; Rajeev M Gadgil; Ajay R Bhoosreddy; Bhushan S Ahire; Varun R Kunte; Manila R Shinde (Wolters Kluwer Medknow Publications, 2015)
Introduction: Hepatitis B is a major health problem worldwide and more serious in India. Hepatitis B virus has only human reservoir, and it is easily transmitted to one another. In the field of dentistry, it involves with saliva and blood, and it also involves many accidental injuries. Dentist with their associates are more prone to get infected. Aim: To assess the level of understanding and awareness about hepatitis B infection among the dental undergraduate and postgraduate students, institutional staff of a reputed dental college, dental practitioners, dental auxiliary, and paramedics of a city in Maharashtra. Materials and Methods: A cross-sectional survey was carried out in 350 subjects using a self-administered pretested questionnaire containing 15 questions on awareness about prevention and transmission, vaccination status of hepatitis B, awareness of postexposure prophylaxis (PEP), and complications associated with hepatitis B. Descriptive analysis was carried out and was presented as a percentage. Results: The response rate was 100% (n = 350). Majority of the undergraduate and postgraduate students, college staff, and dental practitioners were aware of hepatitis B infection, its vaccination, and its importance but knowledge and awareness regarding the incubation period, PEP, and complications associated were less. Dental auxiliary staff has the minimal knowledge and awareness about hepatitis B infection. Conclusion: Overall good knowledge and awareness are observed among the undergraduate and postgraduate students, college staff, and in the dental practitioners. The auxiliary and paramedical staffs are minimally aware.